Factors influencing students' proficiency development in the fraction domain: the role of teacher cognitions and behaviour. Issue 1 (2nd January 2019) - Koopman, Maaike; Thurlings, Marieke; den Brok, Perry
Abstract: In this study, we investigated which teacher characteristics influence student proficiency development regarding fractions in Grade 5 of Dutch primary education. At least three domains of research (i.e. perspectives) on effective teaching can be distinguished: studies focusing on teachers' background characteristics, on their knowledge and conceptions regarding the subject they are teaching and on the domain-specific and general pedagogical characteristics of their teaching. In this study, effects of the three perspectives on student fraction proficiency were examined simultaneously using multilevel analyses. Findings revealed that teachers' age and experience in the upper grades, their pedagogical content knowledge and the degree of student participation in their lessons had positive effects. Their subject matter knowledge, quality of their concept maps and the richness of the mathematics in their lessons had negative effects. Thus, effects were found pertaining to all three perspectives on teachers and their teaching we included in our study.